2023
DOI: 10.1101/2023.11.29.569220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spartin-mediated lipid transfer facilitates lipid droplet turnover

Neng Wan,
Zhouping Hong,
Matthew A. H. Parson
et al.

Abstract: Lipid droplets (LDs) are organelles critical for energy storage and membrane lipid homeostasis, whose number and size are carefully regulated in response to cellular conditions. The molecular mechanisms underlying lipid droplet biogenesis and degradation, however, are not well understood. The Troyer syndrome protein spartin (SPG20) supports LD delivery to autophagosomes for turnover via lipophagy. Here, we characterize spartin as a lipid transfer protein whose transfer ability is required for LD degradation. S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Recently, the protein spartin, found to localize to both LD and endosomal compartment and to act as lipophagy receptor [79], has been shown to have the ability to transfer phospholipids via its senescence domain [80], and it links LD to autophagy machinery to mediate lipophagy [79]. Interestingly, Wan et al revealed that the role of spartin in LD turnover is dependent on its senescence domain, and therefore, it may require spartin lipid transfer activity [80]. However, whether this process happens at ERmitochondria-LD contacts remains to be elucidated.…”
Section: Ld Turnover At Mamsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the protein spartin, found to localize to both LD and endosomal compartment and to act as lipophagy receptor [79], has been shown to have the ability to transfer phospholipids via its senescence domain [80], and it links LD to autophagy machinery to mediate lipophagy [79]. Interestingly, Wan et al revealed that the role of spartin in LD turnover is dependent on its senescence domain, and therefore, it may require spartin lipid transfer activity [80]. However, whether this process happens at ERmitochondria-LD contacts remains to be elucidated.…”
Section: Ld Turnover At Mamsmentioning
confidence: 99%
“…Recently, the protein spartin, found to localize to both LD and endosomal compartment and to act as lipophagy receptor [79], has been shown to have the ability to transfer phospholipids via its senescence domain [80], and it links LD to autophagy machinery to mediate lipophagy [79]. Interestingly, Wan et al .…”
Section: Mitochondria–er‐associated Membranes (Mams): a Key Platform ...mentioning
confidence: 99%
See 1 more Smart Citation